QUALITY OF THE LEARNING SYSTEM AND SERVICES AT THE INSTITUTE OF TEACHER EDUCATION (ITE) - Syed Ismail Syed Mustapa; Azahar Aziz; Shamsazila Sa’aban; Salmiah Md.Salleh (Journal Civics And Social Studies, 2023)
he raduate racer Stud is an annual sure conducted to deterine graduates satisfaction ith the ualit of the learning sste and serices roided after the hae coleted their studies his stud ais to sure Institute of eacher ducation I graduates ersecties on eight asects nael the content of the stud rograe assessent sste counselling and career guidance serices teaching staff infrastructure facilities skills acuired fro studies selfrearedness and ercetion of Is reutation A total of graduates fro I causes hae ansered the distriuted instruent he sures findings suggest that the graduates oerall ieoint on the eight asects of the stud is at a high leel ith a ean score of S he ean for each asect is also high hich is the ersectie on selfrearedness ean S skills otained fro studies ean S ercetion of Is reutation ean S teaching staff ean S stud rograe content ean S assessent sste ean S counselling and career guidance serices ean S and infrastructure facilities ean S olloing that the studs findings suggest that graduates ai to continue their education at a higher leel he studs findings also suggest that an graduates shoed a illingness to continue sering in the teaching rofession he researcher roosed increasing the ale student recruitent uota for the achelor of eaching rograe Siilarl infrastructure facilities need to e enhanced urtherore I graduates ust erace the oortunit to continue their studies at a higher leel Siultaneousl I ust accelerate the ileentation of Masters and octoral stud rograes at I inall the researcher recoended that additional research e conducted on the influence of arts of the I learning sste and serices to iroe the teacher education programe.